Simulation study on adsorption characteristics of lignite to mine gas - Jiayun Lun; Yinghao Sun; Junling Ding; Huijie Song; Zhaohong Zhang (AIP Advances, 2022)
This study aims at investigating the adsorption mechanism of CO2, CH4, CO, and N2 mine gases and oxygen-containing functional groups in lignite. Thus, density functional theory and grand canonical Monte Carlo simulation methods were used to determine the adsorption energy, configuration, isotherm, and isosteric heat as well as the diffusion coefficient of gas in lignite. The results showed that the adsorption capacity of CO2 molecules and oxygen-containing functional groups was greater than that of CH4, CO, and N2. The order of the absolute value of the adsorption energy of each oxygen-containing functional group of each gas molecule on the lignite surface model was as follows: carboxyl > hydroxyl > carbonyl > ether bond. The adsorption isotherms of the four gases (CO2, CH4, CO, and N2) in the lignite molecular structure model were consistent with the Langmuir adsorption isotherm model. The relationship between the adsorption amount of the four gases in the lignite structure model was CO2 > CH4 > CO > N2. In addition, the adsorption capacity of the four gases decreased as the temperature increased. The CO2 isosteric heat of adsorption was considerably greater than that of CH4, CO, and N2, indicating that the adsorption capacity of the lignite molecular structure model for CO2 was considerably stronger than that of CH4, CO, and N2. The CO2 diffusion coefficient showed the slowest change with the temperature increase, whereas the N2 self-diffusion coefficient showed the fastest change. The following diffusion activation energy sequence was obtained: CO2 < CH4 < CO < N2.